Archaeological evidences are still missing: a comment on Fariña et al. Arroyo del Vizcaíno Site, Uruguay - Suárez, Rafael (2014)
This is a comment on the paper Fariña RA, Tambusso PS, Varela L, Czerwonogora A, Di Giacomo M, Musso M, Bracco R, Gascue A. 2014 Arroyo del Vizcaı´no, Uruguay: a fossil-rich 30-ka-old megafaunal locality with cut-marked bones. Proc. R. Soc. B 281, 20132211